Policy Implementation Village Funds - Ade Risna Sari; Rulam Ahmadi; Ika Agustina; Ira Meiyenti; Tumija Tumija (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
The village fund is the origin of the APBN funds that are given to the village, transferred to the APBD district/city, and used to pay for the upkeep of government, the implementation of development, the development of civil society, and community empowerment. According to the regulations of the Finance Minister, the Minister of Village, Desert Village Development, and Transmigration sets priorities for the use of village money. The 2020 PDTT Permendes No. 13 on priority use of the village fund in 2021 specifies the SDGs (Sustainable Development Goals) as the top priority for the use of village finances. There are issues with the preparation and prioritisation of the village fund of the government of Kadongdong Village, which results from the lack of participation by all members of the community and the village government's lack of transparency towards the public. As a result, the public lacks understanding of how and what the priority programme of the nation's funds is. Based on the occurrence, researchers are eager to learn more about Kadongdong village in Garut's Banjarwangi district's Analysis Success Implementation Policy Priority Fund Village. According to Edward III's thesis, the success of policy execution depends on four factors: communication, resource availability, disposition, and bureaucratic structure. The research's findings indicate that Kadongdong Village's implementation of the village fund policy, which has been noted by researchers in the context of Kadong Dong Village, is not optimal. It is evident from this communication that the government of Kadongdong Village does not include the entire figure of the community in establishing the priority of the village fund.